2012
DOI: 10.5812/jhs.7784
|View full text |Cite
|
Sign up to set email alerts
|

Study the Knowledge, Attitude and Performance of the Health and Cure Centers Staff Regarding Using Communication Skills in Interacting With Clients in Zahedan City, 2012

Abstract: Background: Correct performance in interventions in health and cure systems, increasing patients' satisfaction and promoting the health state, necessitate the need to make a proper and correct communication among health and cure staff with patients. Objectives: This study is performed with the aim of studying the knowledge, attitude and performance of the health and cure centers staff regarding using communication skills in interacting with clients in Zahedan city. Patients and Methods: In this research, 135 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…2 Tooth caries is one of the most common infectious diseases that affects all races, ages, sexes and geographical areas. 1,3 According to the available statistics, the prevalence of dental caries among 12-year-old Iranian students is higher than the global average and, if left untreated, may lead to loss of teeth. 4 Given the importance of the teeth role from a variety of perspectives, attempts should be made to prevent dental Caries, gum diseases and tooth loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Tooth caries is one of the most common infectious diseases that affects all races, ages, sexes and geographical areas. 1,3 According to the available statistics, the prevalence of dental caries among 12-year-old Iranian students is higher than the global average and, if left untreated, may lead to loss of teeth. 4 Given the importance of the teeth role from a variety of perspectives, attempts should be made to prevent dental Caries, gum diseases and tooth loss.…”
Section: Introductionmentioning
confidence: 99%
“…13 Various trials on different aspects of health have demonstrated that, most of the interventional measures based on behavior change models have been more successful in achieving their objectives, and the efficiency of these models in behavior changing has already been proven. 3,14 The promotion of good oral health through evoking behavior changes requires a good insight in the determinants of the behaviors relevant to oral health. 15 TPB is a Social-cognitive decision-making model that provides a useful framework to predict and explain health behaviors.…”
Section: Introductionmentioning
confidence: 99%